Neurological Applications of Celery (Apium graveolens): A Scoping Review - Terence Yew Chin Tan; Xin Yi Lim; Nor Azrina Norahmad; Hemahwathy Chanthira Kumar; Bee Ping Teh; Nai Ming Lai; Ami Fazlin Syed Mohamed (Molecules, 2023)
Apium graveolens is an indigenous plant in the family Apiaceae, or Umbelliferae, that contains many active compounds. It has been used traditionally to treat arthritic conditions, gout, and urinary infections. The authors conducted a scoping review to assess the quality of available evidence on the overall effects of celery when treating neurological disorders. A systematic search was performed using predetermined keywords in selected electronic databases. The 26 articles included upon screening consisted of 19 in vivo studies, 1 published clinical trial, 4 in vitro studies and 2 studies comprising both in vivo and in vitro methods. A. graveolens and its bioactive phytoconstituent, 3-n-butylphthalide (NBP), have demonstrated their effect on neurological disorders such as Alzheimer’s disease, Parkinson’s disease, stroke-related neurological complications, depression, diabetes-related neurological complications, and epilepsy. The safety findings were minimal, showing that NBP is safe for up to 18 weeks at 15 mg/kg in animal studies, while there were adverse effects (7%) reported when consuming NBP for 24 weeks at 600 mg daily in human trials. In conclusion, the safety of A. graveolens extract and NBP can be further investigated clinically on different neurological disorders based on their potential role in different targeted pathways.